Astronomy 2e - Fraknoi, Andrew; Morrison, David; Wolff, Sidney C. (Open textbook library., 2022)
Designed to meet the scope and sequence of your course, Astronomy 2e is written in clear non-technical language, with the occasional touch of humor and a wide range of clarifying illustrations. It has many analogies drawn from everyday life to help non-science majors appreciate, on their own terms, what our modern exploration of the universe is revealing. The book can be used for either a one-semester or two-semester introductory course. The second edition has been updated according to new exploration and discoveries. The second edition also includes a significant amount of new art and images. The first edition of Astronomy by OpenStax is available in web view here.